2004
DOI: 10.1111/j.1523-1755.2004.00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hemodialysis on endogenous plasma and muscle carnitine levels in patients with end-stage renal disease

Abstract: Long-term hemodialysis treatment is associated with a significant reduction in endogenous plasma and muscle L-carnitine levels and a significant increase in plasma acylcarnitines. The majority of the change in plasma L-carnitine concentrations occurs within the first few months of hemodialysis, while muscle levels continue to decline after 12 months of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 29 publications
1
89
1
Order By: Relevance
“…13,15,17,18 Recent research by our group has investigated the relationship between the duration of haemodialysis treatment (dialysis age) and carnitine status. 21 The study demonstrated a signi¢cant negative correlation between plasma L-carnitine concentrations and dialysis age, with the majority of the reduction in L-carnitine concentrations occurring within the ¢rst few months of haemodialysis treatment. The decline in plasma L-carnitine with increasing dialysis age was accompanied by a similar reduction in plasma acetyl-L-carnitine concentrations (acetyl-L-carnitine is the most abundant acylcarnitine in the body); however, acetyl-L-carnitine concentrations remained above the reference range for healthy individuals.…”
Section: Introductionmentioning
confidence: 97%
“…13,15,17,18 Recent research by our group has investigated the relationship between the duration of haemodialysis treatment (dialysis age) and carnitine status. 21 The study demonstrated a signi¢cant negative correlation between plasma L-carnitine concentrations and dialysis age, with the majority of the reduction in L-carnitine concentrations occurring within the ¢rst few months of haemodialysis treatment. The decline in plasma L-carnitine with increasing dialysis age was accompanied by a similar reduction in plasma acetyl-L-carnitine concentrations (acetyl-L-carnitine is the most abundant acylcarnitine in the body); however, acetyl-L-carnitine concentrations remained above the reference range for healthy individuals.…”
Section: Introductionmentioning
confidence: 97%
“…In incident hemodialysis (HD) patients, the plasma carnitine level decreases within the first week of the treatment, with a continual decrease over the first 12 months of treatment [4]. The carnitine content of the skeletal muscle also decreases in hemodialysis patients and is inversely correlated with time on HD [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Repeated dialysis treatment over an extended period results in a deficiency of tissue carnitine. 9 Carnitine insufficiency in patients on long-term HD affects dialysis-related symptoms such as skeletal myopathy, cardiomyopathy, poor exercise performance, anemia, and dialytic complications, such as hypotension, cramps, weakness, and fatigue, 10,11 which decrease dialysis tolerance and reduce the long-term survival rate. Consequently, carnitine therapy has been used and extensively studied in patients with ESRD.…”
Section: Discussionmentioning
confidence: 99%